CURRICULUM 2013 IN THE PHILOSOPHY OF TRADITIONAL EDUCATION PERSPECTIVES - FAHRIAN FIRDAUS SYAFII; ABDUL RAHMAT; RUSMIN HUSAIN (International Journal of Innovations in Engineering Research and Technology, 2021)
This study aims to find out about the 2013 curriculum in the perspective of traditional educational philosophy, . Then, this research was carried out through literature study by collecting and reviewing a number of literature in the form of journals and books related to traditional educational philosophies. In data collection, researchers read various literature in order to obtain relevant information and in accordance with the research under study. Furthermore, for data analysis, namely by using critical analysis which is an interpretation of the text and addressing the meaning behind an event. Based on the results of the study, it shows that, in the perspective of essentialism, the curriculum is subject centered matter centered on subjects and based on 3R, namely; writing, reading and arithmetic. Although essentialism is a conservative or traditional school, this flow is able to bring and bring about success in the world of education. One of the goals of education in the 2013 curriculum is to develop the intellectual abilities of students and the knowledge that becomes the content is essential skills, mastery of the concepts and principles of subjects.